Factors Affecting Reading Interest Among Children In The Village Of Pidodo Kulon - Silvi Setia Dewi; Fatimah Azzahra Putri Bachtiar; Lailatul Nazilah; Rahma Ardinitia Cahya; Hygidia Rizqia Novika; Jannatul Firdausi Nuzula; Syahrizal Nashwanpramudito; Irma Istiariyani (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This study aims to identify the factors influencing children’s reading interest in Pidodo Kulon Village. A qualitative approach was employed using semi-structured interviews and observations, involving 11 informants consisting of teachers, the principal, village officials, parents, and elementary school students. The findings reveal that children’s low reading interest is shaped by both internal and external factors. Internal factors include low learning motivation, the absence of early reading habits, and a greater attraction to gadgets than books. External factors consist of parenting patterns of parents working abroad, limited family support in fostering literacy, insufficient access to reading materials, and school curricula that have not fully promoted literacy development. The revitalization of the village Reading Corner has become a positive initial step to address this issue, although further development of more diverse and age-appropriate book collections is still needed. This study emphasizes that improving children’s reading interest requires active collaboration between families, schools, and the community to create a supportive and sustainable literacy environment.